Spectre and Meltdown processor flaws threaten billions of computers and mobile devices. Issue 1 (January 2018) - Unknown
Abstract : Flaws in the way that a number of processor types execute instructions could make billions of devices – including cloud servers, PCs and mobile platforms – vulnerable to hacking.